2017
DOI: 10.1515/otmcj-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Cost and time performance of traditional-, direct labour- and management-procured public projects in Ondo State, Nigeria

Abstract: Procurement method over time has proven to have significant influence on the successful delivery of construction projects. Making the right decision in the selection of a procurement option to adopt is therefore crucial if a project is to succeed. This study therefore assessed the cost and time performance of selected public building projects procured using traditional, direct labour and management procurement options in Ondo State, Nigeria. A pro forma was used to gather cost and time data from government pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The findings from this study align with research conducted by (Jimoh, Oyewobi, & Aliu, 2016) and (Aghimien, Osanyinro, & Adegbembo, 2016) which focused on evaluating procurement methods in the Nigerian construction industry. These studies identified factors such as quality, cost, duration, and project complexity as significant influencers in the choice of procurement method.…”
Section: Procurement Methods Used By Naz For the Construction Of Cons...supporting
confidence: 82%
“…The findings from this study align with research conducted by (Jimoh, Oyewobi, & Aliu, 2016) and (Aghimien, Osanyinro, & Adegbembo, 2016) which focused on evaluating procurement methods in the Nigerian construction industry. These studies identified factors such as quality, cost, duration, and project complexity as significant influencers in the choice of procurement method.…”
Section: Procurement Methods Used By Naz For the Construction Of Cons...supporting
confidence: 82%
“…Examining 32 LoPS projects in Nigeria, Akinkunmi et al (2018) found a 2% cost saving overall. Given the harsh economic conditions in many countries including Nigeria and the 4.87% saving in educational projects procured through other routes in Nigeria found in Aghimien et al (2017), it can be argued that the saving LoPS provides is significant. According to Ogunsanmi (2013), the poor economic climate of Nigeria contributes to the increased adoption of LoPS.…”
Section: Ijppm 737mentioning
confidence: 99%
“…(2018) found a 2% cost saving overall. Given the harsh economic conditions in many countries including Nigeria and the 4.87% saving in educational projects procured through other routes in Nigeria found in Aghimien et al. (2017), it can be argued that the saving LoPS provides is significant.…”
Section: Literature Reviewmentioning
confidence: 99%